Driving MSME Performance in the Digital Era: Financial Literacy and E-Commerce Adoption in Minahasa - Pebisitona Mesajaya Purba (Al Dzahab, 2026)
Purpose: This study aims to examine the role of financial literacy and e-commerce adoption in driving the performance of Micro, Small, and Medium Enterprises (MSMEs) in Minahasa Regency, North Sulawesi, within the context of the digital economy. Design/Methodology/Approach: This research employs a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Primary data were collected through structured questionnaires distributed to MSME actors selected using a stratified random sampling technique. Financial literacy was measured through indicators of basic financial knowledge, business financial management, financial planning and control, and investment knowledge. E-commerce adoption was assessed through platform utilization, digital marketing capability, operational management, and performance evaluation. MSME performance was measured through financial performance, operational performance, marketing performance, and business sustainability. Findings: The results of the outer model evaluation indicate that the measurement model meets the criteria for validity and reliability. However, the inner model results show that financial literacy and e-commerce adoption do not have a significant effect on MSME performance. In addition, the interaction between financial literacy and e-commerce adoption also produces a negative but insignificant coefficient. The relatively low R-square value suggests that MSME performance is influenced by a broader business ecosystem, including infrastructure availability, access to capital, government policies, and market dynamics. Research Implications: The findings highlight the importance of a holistic and integrative strategy in improving MSME performance. Efforts to strengthen MSMEs should not only focus on increasing financial literacy and adopting digital technologies but should also consider broader ecosystem factors that support business growth and sustainability.